Chest pain and a left parasternal soft tissue swelling in an immunocompetent refugee with disseminated tuberculosis. (January 2020) - Mondoni, Michele; Centola, Marco; Viganò, Ottavia; Ferrarese, Maurizio; Codecasa, Luigi; D'Arminio Monforte, Antonella; Carugo, Stefano; Centanni, Stefano; Lipman, Marc; Sotgiu, Giovanni
Highlights: Tuberculosis in foreign-born immunocompetent individuals. Cardiac tuberculosis is a rare condition. High incidence of extrapulmonary tuberculosis in migrant patients. Abstract: An immunocompetent migrant with chest pain was admitted to an Italian hospital. Computed tomography showed a left pectoral abscess and osteomyelitis of the sternum. The infection had spread into the anterior mediastinum near to the pericardium and the heart, where an atrial mass was confirmed by echocardiography. Disseminated tuberculosis was diagnosed.